Origanum vulgare essential oil in the treatment of skin experimental sporotrichosis (Research, Society and Development, 2023)
Sporotrichosis has emerged as a major zoonotic disease in large urban centers. Its treatment is performed through the administration of antifungals for prolonged periods, being restricted the active ingredients used, requiring other therapeutic options. Thus, the present study aims to determine the activity of Origanum vulgare oil in the treatment of experimental cutaneous sporotrichosis. Forty male Wistar rats were divided into four experimental groups, inoculated with S. brasiliensis and submitted to 30 days of treatment. Weekly, the animals were evaluated and two animals per group were euthanized to collect material to analyze the development of the disease and the evolution of the different treatments. At the end of 30 days, the remaining animals were euthanized and also had biological materials collected for analysis. The animals belonging to the itraconazole and control groups did not show complete disappearance of clinical signs during the experiment. The animals treated with the essential oil did not show any microscopic alteration in the kidneys, liver and spleen during the whole period. The fungus was retroisolated from the regional lymph node of all animals of all groups in the four necropsies performed.